2012
DOI: 10.1523/jneurosci.4479-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

PI3-kinase/Akt Pathway-Regulated Membrane Insertion of Acid-Sensing Ion Channel 1a Underlies BDNF-Induced Pain Hypersensitivity

Abstract: Central neural plasticity plays a key role in pain hypersensitivity. This process is modulated by brain-derived neurotrophic factor (BDNF) and also involves the type 1a acid-sensing ion channel (ASIC1a). However, the interactions between the BDNF receptor, tropomyosinrelated kinase B (TrkB), and ASIC1a are unclear. Here, we show that deletion of ASIC1 gene suppressed the sustained mechanical hyperalgesia induced by intrathecal BDNF application in mice. In both rat spinal dorsal horn neurons and heterologous ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
109
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(116 citation statements)
references
References 77 publications
(105 reference statements)
6
109
0
Order By: Relevance
“…ASIC1a was found to be present in all fractions in which the mitochondrial proteins VDAC and Cyt C were enriched (Figure 4a). Consistent with previous findings, 8,28 we noticed that ASIC1a was also present in the endoplasmic reticulum (ER) fractions, indicated by the enrichment of protein disulfide isomerase (PDI) (Figure 4a). …”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…ASIC1a was found to be present in all fractions in which the mitochondrial proteins VDAC and Cyt C were enriched (Figure 4a). Consistent with previous findings, 8,28 we noticed that ASIC1a was also present in the endoplasmic reticulum (ER) fractions, indicated by the enrichment of protein disulfide isomerase (PDI) (Figure 4a). …”
Section: Resultssupporting
confidence: 92%
“…Recent evidence suggested an intracellular perinuclear location of ASIC1a in both transfected Chinese hamster ovary (CHO) cells and cultured mouse cortical neurons. 8,28 The association between ASIC1a and ANT suggested that some intracellular ASIC1a proteins might be localized to mitochondria. To verify the mitochondrial localization of ASIC1a, we first made crude cellular fractionations from mouse cortices by sucrose gradient centrifugation at different speeds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…BDNF increased ASIC1a cell surface expression by inducing phosphorylation of the N-terminal residue Ser25 via the phosphoinositide 3-kinase-protein kinase B cascade. Intrathecal injection of BDNF induced mechanical hyperalgesia, which was prevented by ASIC1a disruption (Duan et al, 2012).…”
Section: Tissue Distribution Cellular Functions and Physiologimentioning
confidence: 95%
“…Administration to the CNS of the spider toxin PcTx1, a specific inhibitor of ASIC1a, diminished pain behavior, further demonstrating the important role of central ASIC1a in pain sensation (Duan et al, 2007;Mazzuca et al, 2007). A recent study showed that ASIC1a in the spinal cord is the target of brain-derived neurotrophic factor (BDNF) (Duan et al, 2012). BDNF increased ASIC1a cell surface expression by inducing phosphorylation of the N-terminal residue Ser25 via the phosphoinositide 3-kinase-protein kinase B cascade.…”
Section: Tissue Distribution Cellular Functions and Physiologimentioning
confidence: 99%